O funcionamento enunciativo da argumentação: a prova de redação do ENEM - Fernandes, Luana Aparecida Matos Leal (2020)
The aim of this thesis is to comprehend the complex enunciative relation established in and by the ENEM exam and thus, analyze and expose the functioning of argumentation in such exam. In this perspective, we believe there is a specific functioning in the construction of argumentation in the essay proposed by the exam, so we have asked ourselves how such functioning occurs, considering the implied intersubjectivity present in this assessing exam. Our starting point was the hypothesis that argumentation in the writing process of the essay at ENEM exam involves the necessity of candidates/authors fulfilling textual and discursive restrictions that are part of the essay guidelines, written on the exam. In order to support our research theoretically, we joined the studies carried out by Émile Benveniste about language and its functioning, which emphasis is on the interlocutive relation. In our perspective, in the essay of ENEM exam, there is a complex situation of enunciation, in which the candidate/author, while enters the game of the essay, submits himself/herself to the enunciation of the exam and has to position himself/herself to the enunciation proposed, assuming, thus, the role of collocutor established by the exam. It is from this position that the candidate/author must make an interpretation of the theme and the motivating written texts. This interpretation leads him/her to re(produce) the written text, attending a figurative board established by the ENEM exam. As a result, assuming such position, the candidate re(produces) a written enunciation based on the demanding of the exam, establishing with an institutional you an intersubjective relation in the reading process of the essay proposed and the production of the written text, aiming at a co-construction of meaning in order to obtain a successful reply. Considering this position, in order to answer our research question, we initially engaged in the study of ENEM exam as a public policy of assessment, relying on official documents about the implementation and establishment of this exam in Brazil. Then, we present the essay proposed by the ENEM exam, throughout institutional documents that describe the exam and its assessment criteria. After this study, our analysis happened following two stages. In the first stage, we have studied and analyzed the essay proposal of ENEM exam in 2017, searching to understand the enunciation established there. In the second stage, we have analyzed the essays produced by the candidates/authors of the ENEM exam in 2017, considering the discursive relation presented in the exam and the enunciative relation established. At this point, we have sought to analyze in the essays, the textual path produced by the candidates/authors to attend the demanding of the exam as an attempt to obtain a good score. Therefore, as a result of the analysis, we defend that “argumentation”, in such a complex situation of enunciation, puts the candidate/author in a situation in which he/she does not “defend his/her point of view”, but rather, the point of view implied by the enunciation established. This argumentation is also related to a textual elaboration of the essay throughout the management of standard and institutionalized language and mobilization of personal language experience that altogether re(produces) a certain effect of co-reference with the enunciation established in the exam.